Navigating standards, encouraging interconnections: infrastructuring digital health platforms. Issue 8 (2nd July 2020) - Williams, Ros; Will, Catherine; Weiner, Kate; Henwood, Flis
ABSTRACT: Apps, websites and networked devices now offer to help consumers produce, access and share health knowledge, precipitating social scientific concern over the consequences of these so-called digital health platforms. This paper makes a novel contribution to this literature, taking up a recent call from Plantin et al. to adopt an infrastructural lens in exploring platforms. It argues, through empirical analysis of digital health platforms of different sizes, ages and nationalities, that this conceptual tool is necessary to surface the work entailed in creating and sustaining digital health platforms. Additionally, we suggest that the social scientific literature on platforms – and initial efforts to explore their infrastructural qualities – frequently focus too strongly on the dominant technology companies. Instead, we emphasise the value of drawing emergent companies' platforms into empirical purview through returning to some of the infrastructures literature that informs Plantin et al. – particularly Susan Leigh Star and colleagues. We demonstrate empirically the importance of looking at standards as part of infrastructure building, and the broader set of interconnections between different actors and materials within an infrastructure. In doing so, we demonstrate the value of an infrastructural lens for understanding the density of interconnections that characterise digital health and propose some orientating questions for further enquiry into the infrastructural qualities of platforms.